2006
DOI: 10.1016/j.jfa.2006.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotics of repeated interaction quantum systems

Abstract: A quantum system S interacts in a successive way with elements E of a chain of identical independent quantum subsystems. Each interaction lasts for a duration τ and is governed by a fixed coupling between S and E. We show that the system, initially in any state close to a reference state, approaches a repeated interaction asymptotic state in the limit of large times. This state is τ -periodic in time and does not depend on the initial state. If the reference state is chosen so that S and E are individually in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
114
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(121 citation statements)
references
References 15 publications
6
114
1
Order By: Relevance
“…In this case however, the (random) channels Φ βn do not have in general a common invariant state, so one has to look at ergodic limits. We use here the machinery developed by L. Bruneau, A. Joye and M. Merkli in [6] (see [7,5] for additional results in this direction). For the sake of completeness, let us state their main result.…”
Section: Repeated Interactions With Random Auxiliary Statesmentioning
confidence: 99%
“…In this case however, the (random) channels Φ βn do not have in general a common invariant state, so one has to look at ergodic limits. We use here the machinery developed by L. Bruneau, A. Joye and M. Merkli in [6] (see [7,5] for additional results in this direction). For the sake of completeness, let us state their main result.…”
Section: Repeated Interactions With Random Auxiliary Statesmentioning
confidence: 99%
“…Such models have been analyzed in [BJM1,WBKM] (see also [BJM2] for a random setting). It was shown in [BJM1] that the RI dynamics gives rise to a Markovian effective dynamics on the system S and drives the latter to an asymptotic state, at an exponential rate (provided S has a finite dimensional Hilbert space). The limit τ → 0 with appropriate rescaling of the interaction Hamiltonian H SE was studied in [APa,AJ2].…”
Section: Repeated Interactionsmentioning
confidence: 99%
“…They have shown that these "deterministic" dynamics give rise to quantum stochastic differential equations in the continuous limit. Since that result, some interest has been found in the repeated quantum interaction model in itself (cf [AJ1], [AJ2], [BJM1], [BJM2], [BJM3]) and several physical works are in progress on that subject (for example [AKP]). These repeated interaction models are interesting for several reasons: -they provide a quantum dynamics which is at the same time Hamiltonian and Markovian, -they allow to implement easily the dissipation for a quantum system, in particular they are practical models for simulation.…”
Section: Introductionmentioning
confidence: 99%